Assistance with Empirical Assessment of Increasing Community Welfare Through Village Fund Management - Karfin, Karfin; Hasrun, Andi; Rokhimah, Rokhimah; Masseni, Masseni; Kahinah, Dwi Iin (Teumulong: Journal of Community Service, 2024)
This service evaluates the impact of village fund management on improving community welfare in Warmon Kokoda Village, Mayamuk District, Sorong Regency. By applying Islamic economic principles that emphasize justice, transparency, and accountability, this study uses qualitative and quantitative approaches to assess changes in various indicators of community welfare, including education, health, income, and access to social services. Through surveys and interviews with local residents, the results of the service show a real increase in community welfare, which is driven by effective and participatory fund management. These findings provide empirical evidence supporting the use of village funds as a tool for village development and community empowerment, recommending management strategies that can be adapted to different contexts to achieve broader and more inclusive outcomes.